DUAL ANTIPLATELET THERAPY IN THE REAL CLINICAL PRACTICE - G. N. Guseva; T. V. Pavlova; I. L. Voronova; S. M. Chohlunov (Столичная издательская компания, 2015)
Aim. To evaluate an adequacy of dual antiplatelet therapy (DAPT) in patients with acute coronary syndrome (ACS) with ST segment elevation and bare metal stent implantation after hospital discharge.Material and methods. 311 patients with ACS with ST segment elevation were included into the study. All of them underwent percutaneous coronary intervention with bare metal stent implantation. The information was obtained by the telephone survey.Results. 54.5% of patients received DAPT during 12 months. 43.8% of patients also received combination of clopidogrel and acetylsalicylic acid, but changed medicinal products of clopidogrel due to different reasons. 1.7% of patients received acetylsalicylic acid only.Conclusion. More than 50% of patients received recommended DAPT at that they preferred generic drugs of clopidogrel original one.